Heterobimetallic metallation studies of N, N-dimethylphenylethylamine (DMPEA): benzylic C–H bond cleavage/dimethylamino capture or intact DMPEA complex12. Issue 12 (26th February 2015) - Kennedy, Alan R.; Mulvey, Robert E.; Ramsay, Donna L.; Robertson, Stuart D.
Abstract : The cleave and capture capacity of various bimetallic amido–alkyl mixtures is illustrated through reaction with the deprotonation sensitive N, N -dimethylphenylethylamine. Abstract : Reaction of the sodium monoamido-bisalkylzincate [(TMEDA)Na(TMP)(Bu t )Zn(Bu t )] (TMEDA is N, N, N ′, N ′-tetramethylethylenediamine; TMP is 2, 2, 6, 6-tetramethylpiperidide) and the related lithium zincate [(PMDETA)Li(TMP)Zn(Bu t )2 ] (PMDETA is N, N, N ′, N ′′, N ′′-pentamethyldiethylenetriamine) with the sensitive bio-relevant scaffold N, N -dimethylphenylethylamine, DMPEA, afforded the crystalline complexes [(TMEDA)Na(TMP)(NMe2 )Zn(Bu t )] and [(PMDETA)Li(NMe2 )Zn(Bu t )2 ], respectively, both of which have been characterized by NMR spectroscopic and X-ray crystallographic studies. Made by reaction of a LiTMP–(TMP)Al(Bu i )2 mixture with DMPEA, a third dimethylamino-containing crystalline complex, the aluminate [(THF)Li(TMP)(NMe2 )Al(Bu i )2 ] has been similarly characterized. All three complexes can be regarded as products of cleave and capture chemistry whereby metallation at the benzylic position of DMPEA has led to a β-elimination of an anionic Me2 N fragment that has been captured by a charge balancing cationic heterobimetallic entity. While a metallated intermediate prior to the elimination has proved elusive in all of these reactions, DMPEA has been captured fully intact in the novel Lewis acid–Lewis base crystalline complex [DMPEA·Li(TMP)Zn(Me)2 ], which has also been characterized by the aforementioned techniques.